The gait analysis at children aged 6-18 years old - a comprehensive review - Nuriu, Denis; Spahiu, Elton; Bendo, Aida (Edelweiss Applied Science and Technology, 2024)
Gait analysis is an essential method for evaluating children’s locomotor development because it offers information on their social, cognitive, and physical growth. It’s crucial to understand how children between the ages of 6 and 18 walk because a number of things affect their mobility during this stage of development. The purpose of this review is to assess the body of research on gait analysis in children ages 6 to 18, with an emphasis on the consequences of anomalies in gait, the efficacy of evaluation techniques, and intervention tactics. A thorough literature study was carried out, including information from clinical research, peer-reviewed publications, and developments in gait analysis technology. The examination took into account a number of evaluation instruments, such as force plates, motion capture devices, and observational gait analysis. The results show that gait abnormalities are significantly more common in this age range, especially in children with developmental problems. More accurate assessments are now possible thanks to developments in gait analysis technology, which also makes it easier to create focused intervention plans that enhance mobility and general quality of life. The significance of early detection of gait abnormalities and the function of interdisciplinary treatment approaches are covered in the review. In order to maximize care for impacted children, it highlights the necessity for doctors to combine clinical judgment with technical improvements. In conclusion, gait analysis is crucial to comprehending how youngsters between the ages of 6 and 18 acquire their locomotor skills. The long-term impacts of gait abnormalities must be investigated more, and intervention techniques must be improved, in order to encourage children with these issues to have healthier and more active lives.